Biomimetic, bioresponsive, and bioactive materials : an introduction to integrating materials with tissues - Santin, Matteo; Phillips, Gary (Wiley, 2012)
"This comprehensive introduction to biomaterials discusses how materials are selected, designed, and modified for integration with living tissue. Biomaterials have applications in tissue engineering, medical devices, orthopedics, and other areas. This guide examines the physico-chemical properties of widely used biomaterials and cites examples of their uses in different clinical applications. Topics covered include soft and hard tissue replacement; biointeractive metals, polymers, and ceramics; and in vitro, in vivo, and ex vivo biocompatibility tests and clinical trials. This text is for students as well as professionals new to the field"-- Anotace od vydavatele
Keywords: biomimetické materiály; biologické materiály; syntetické materiály; biopolymery; polymery; tkáně; tkáňové inženýrství; biokompatibilita; biomimetic materials; biological materials; synthetic materials; biopolymers; polymers; tissues; tissue engineering; biocompatibility; kolektivní monografie; collective monographs